2012
DOI: 10.1111/j.1365-294x.2012.05723.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of fungal communities among and within decaying logs, revealed by 454 sequencing

Abstract: Owing to previous methodological limitations, knowledge about the fine-scale distribution of fungal mycelia in decaying logs is limited. We investigated fungal communities in decaying Norway spruce logs at various spatial scales at two environmentally different locations in Sweden. On the basis of 454 pyrosequencing of the ITS2 region of rDNA, 1914 operational taxonomic units (OTUs) were detected in 353 samples. The communities differed significantly among logs, but the physical distance between logs was not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
141
6
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 73 publications
11
141
6
9
Order By: Relevance
“…This is inconsistent with the findings of fructification pattern studies, which indicated that the abundance of fruiting bodies was highest at intermediate stages of decay (Heilmann-Clausen 2001; Hoppe et al 2014). However, the fact that fungal OTU richness increased with losses of mass and density (i.e., as the decay class increased) is in agreement with the results of previous studies on spruce deadwood that used molecular techniques (Kubartova et al 2012;Rajala et al 2012). The discrepancy between these findings may be due to the fact that many fungi tend to reside as vegetative mycelia in deadwood and therefore do not develop fruiting bodies (Kubartova et al 2012).…”
Section: Fungal Diversity and Community Compositioncontrasting
confidence: 94%
See 4 more Smart Citations
“…This is inconsistent with the findings of fructification pattern studies, which indicated that the abundance of fruiting bodies was highest at intermediate stages of decay (Heilmann-Clausen 2001; Hoppe et al 2014). However, the fact that fungal OTU richness increased with losses of mass and density (i.e., as the decay class increased) is in agreement with the results of previous studies on spruce deadwood that used molecular techniques (Kubartova et al 2012;Rajala et al 2012). The discrepancy between these findings may be due to the fact that many fungi tend to reside as vegetative mycelia in deadwood and therefore do not develop fruiting bodies (Kubartova et al 2012).…”
Section: Fungal Diversity and Community Compositioncontrasting
confidence: 94%
“…However, the fact that fungal OTU richness increased with losses of mass and density (i.e., as the decay class increased) is in agreement with the results of previous studies on spruce deadwood that used molecular techniques (Kubartova et al 2012;Rajala et al 2012). The discrepancy between these findings may be due to the fact that many fungi tend to reside as vegetative mycelia in deadwood and therefore do not develop fruiting bodies (Kubartova et al 2012). Only a small proportion of the sequences obtained from deadwood of Picea abies were assignable to Ascomycota, though the ratio of taxonomically assigned OTUs was balanced to Basidiomycota.…”
Section: Fungal Diversity and Community Compositionsupporting
confidence: 91%
See 3 more Smart Citations